To vape or not to vape? Preliminary results from a qualitative survey of smokers - Aparna Mathur; Roger Bate (American Enterprise Institute (AEI), 2019)
A recent survey found that a higher percentage of sampled smokers had tried vaping in the UK, relative to the US, especially among those who claimed they had tried to quit smoking previously.
Keywords: A; 330; United Kingdom (UK); e-cigarettes